Recent advances in soil glyphosate contamination and removal - Ferreira, Isabela Natália da Silva; Andrade, Rosileide Fontenele da Silva; Takaki , Galba Maria of Campos (Seven Editora, 2023)
The soil has been constantly exposed to a variety of contaminants and their mixtures in various concentrations, organic/inorganic chemical exposure, which mainly includes pesticides and their mixtures of monomers), which contaminate the soil to a greater extent and can also be transported within the soil and transfer the mixed contaminants, integrating into the food chain and passing through different trophic levels,  causing health effects of organisms exposed to them. Pesticides are chemical compounds used to eliminate pests. They are chemical or biological agents, which weaken, incapacitate and kill pests. The emerging contaminant glyphosate (N-(phosphonomethyl)glycine) is widely used in agriculture in several countries. It is considered the most widely used herbicide in the world, as well as being one of the most harmful to human health. This compound is used to control harmful or invasive weeds. Glyphosate is the best-selling active ingredient in Brazil, with 195,056 tons sold in 2018. Brazil stands out for the massive agricultural use of glyphosate. An increasing number of countries have begun to restrict/ban the use of glyphosate-based products, such as Germany, Austria, Bulgaria, Colombia, and Costa Rica, among others, based on evidence already available on the direct incidence of glyphosate at various levels of the global ecosystem, as well as favoring the emergence of serious problems in human health. In this sense, the present study emphasizes the importance of knowing the main properties of pesticides and the study in search of efficient technological advances for the recovery of soils impacted by the use of glyphosate. DOI:https://doi.org/10.56238/alookdevelopv1-067